amorphous wrote:
If a + b = 20, then (a + b/2) + (b + a/2) =
A) 10
B) 20
C) 30
D) 40
E) 50
Here's another approach:
GOAL: find the value of (a + b/2) + (b + a/2)
GIVEN: a + b = 20
Let's take some values of a and b that satisfy the equation a+b = 20, and plug them into our goal expression...
Well, a =
20 and b =
0 satisfy the equation a + b = 20
Now take (a + b/2) + (b + a/2), and replace a and b with
20 and b =
0We get: (a + b/2) + (b + a/2) = (
20 +
0/2) + (
0 +
20/2)
= (20 + 0) + (0 + 10)
= 20 + 10
= 30
Answer: C
Cheers,
Brent